1997
DOI: 10.1080/00984109708984016
|View full text |Cite
|
Sign up to set email alerts
|

Mercury Content in Skin-Lightening Creams and Potential Hazards to the Health of Saudi Women

Abstract: It seems evident from a wealth of scientific research that mercury is toxic. Because of the nature of the Saudi markets, different brands of skin-lightening creams are widely available. In this study, 38 skin-lightening cream samples were collected and analyzed for mercury by inductively coupled plasma spectrometry after an acid digestion procedure. About 45% of the tested skin-lightening cream samples contained mercury at levels well above the FDA's acceptable limit of 1 ppm. These findings are alarming and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(42 citation statements)
references
References 29 publications
0
42
0
Order By: Relevance
“…So it can be concluded that, although occupational exposure and fish consumption (as an effective factors on mercury concentrations) were omitted from the study and all of the participants had the same fish consumption patterns, the mercury level in hair is as a result of other mercury sources like using cosmetic materials or chemical shampoos which potentially effect on Hg levels in hair. In fact, these days cosmetic products (with mercury in their structure) are widely available and frequently used as bleaching agents, skin-lightening cream or other beauty products by women throughout the world [39] and despite the well-known hazards of mercury exposure and the ban against the sale of creams containing mercury in some countries like the United States, these products are widely available in pharmacies, beauty aid stores and cosmetic markets around the world [40].…”
Section: Discussionmentioning
confidence: 99%
“…So it can be concluded that, although occupational exposure and fish consumption (as an effective factors on mercury concentrations) were omitted from the study and all of the participants had the same fish consumption patterns, the mercury level in hair is as a result of other mercury sources like using cosmetic materials or chemical shampoos which potentially effect on Hg levels in hair. In fact, these days cosmetic products (with mercury in their structure) are widely available and frequently used as bleaching agents, skin-lightening cream or other beauty products by women throughout the world [39] and despite the well-known hazards of mercury exposure and the ban against the sale of creams containing mercury in some countries like the United States, these products are widely available in pharmacies, beauty aid stores and cosmetic markets around the world [40].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, mercury is rarely listed as a component of commercially available cosmetics. Al-Saleh and Al-Doush [22] after analyzing 38 commercially available skin lightening creams in 1997 noted that 45% of the tested samples contained mercury at levels far surpassing 1 ppm (the maximum permitted limit by FDA). More recently in 2005, they also analyzed “Fair & Lovely” fairness cream and found traces of mercury that was otherwise not its listed component [23].…”
Section: Discussionmentioning
confidence: 99%
“…Mercury content was determined using the ICP-701 inductively coupled plasma emission spectrometer equipped with the hydride generation system (ATI UNICAM, Cambridge, UK) and 221 XL Gilson autosampler (Gilson, 95400 Villiers le Bel, France) as described previously [51]. Based on the results, two skin-lightening creams were chosen according to their mercury contents.…”
Section: Methodsmentioning
confidence: 99%
“…Highest mercury concentrations were found in 21 skin-lightening samples of the commonly used creams in Saudi Arabia with a mercury range from 1.18 to 77,513 µg/g [51]. This is well above the US Food and Drug Administration limits of 1 µg/g [52].…”
Section: Introductionmentioning
confidence: 98%